A traditional Japanese garden and its lessons for modern times - Ding, Yang; Zueva, Polina; Grazuleviciute-Vileniske, Indre; Yablonska, Hanna; Początko, Marek (Landscape Architecture and Art, 2021)
The study focuses on the origins and characteristics of traditional Japanese landscape design and its features. A comparative analysis of historical Chinese and Japanese horticultural traditions is carried out, as a result of which it is proved that in both cases the basis was religious syncretism with regional characteristics. A comparative analysis of Chinese and Japanese gardens has shown how, over time, they drifted further and further from each other, the Chinese garden continued to improve its hedonistic orientation, while the Japanese garden followed the path of maximum asceticism, the aesthetics of empty space, symbolism, that is, which helped maximize concentration and self-contemplation.